Design and Development of an Augmented Reality Robotic System for Large Tumor Ablation - Yang, Liangjing; Chui, Chee-Kong; Chang, Stephen (International Journal of Virtual Reality, 2009)
An augmented reality based robotic system is proposed for treatment of large liver tumor using multiple overlapping ablations technique. Radiofrequency ablation is a non-resection interventional procedure that minimizes invasiveness and reduces trauma. A single ablation is however limited by the ablation volume coverage. In treatment of tumor with diameter that could be 150mm or more, a single needle insertion will not create sufficient ablation coverage to destroy the entire tumor. As such, multiple insertions are required. The precision and consistency associated with robot assisted surgery coupled with direct augmented reality projection system can better facilitate such treatment. The projection system is equipped with manipulator mechanism and robotic needle insertion arm for multiple insertions and needle deployment. The prototype augmented reality surgical system was evaluated on its abilities in ablating large tumor. Virtual models of the rectangular robot for projector manipulation and robotic needle insertion device were also used to assess the effectiveness of the proposed AR design.